Design and construction of a quick-switching sampling system with a third-generation capability index. Issue 11 (3rd June 2023) - Wang, Zih-Huei; Wu, Chien-Wei; Jhu, Jhen-Jia
Abstract: Acceptance sampling, the most widely used technique in practice, provides rules for making decisions on product acceptance with specified quality standards. A quick-switching sampling (QSS) system, which involves a Normal sampling plan and a Tightened sampling plan with switching rules between them, has recently been discussed. This paper proposes a variables QSS system with parameters (   n N,       n T,       k ) based on a third-generation capability index, which takes process yield and quality loss into consideration. A nonlinear optimization model is formulated to determine the designed plan parameters by minimizing average sample number and subject to the quality and risk levels specified by both the producer and the consumer. The comparison study between the designed sampling system and conventional sampling plan is also conducted in terms of common metrics including operating characteristic curve, average sample number, and average run length. Finally, a practical example is presented along with a step-by-step description of the procedure.